2021
DOI: 10.1111/pace.14195
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of transvenous lead extraction in octogenarians using powered extraction sheaths

Abstract: Background In the aging population equipped with cardiac implantable electronic devices, an increasing number of octogenarians require lead extractions. This patient population is often considered as a high‐risk group for surgical procedures. We, therefore, investigated the safety and efficacy of transvenous lead extraction in octogenarians using powered extraction sheaths. Methods Between January 2013 and March 2017, 403 patients underwent lead extraction at two high‐volume lead extraction centers. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 31 publications
5
11
1
Order By: Relevance
“…This is in line with the literature, where a comparable success rate was found in patients treated with mechanical dilatation, [17][18][19] with laser extraction and with both techniques, irrespective of older age. [4][5][6][7] Previous studies by Kutarski et al 17 and Jacheć et al 18 with larger study groups compared with our study, demonstrated high effectiveness of TLE using non-powered mechanical tools, suggesting the need of only "simple" mechanical tools in elderly patients, probably due to the absence of significant calcification of connecting tissue scar surrounding leads in octogenarians compared to younger patients. 17,18 However, it should be noted that in our study, the mean implant duration was 112 ± 77 months (range 12-377) and patients with recently implanted leads (implant duration < 12 months) or patients with implant duration > 12 months whose leads had been removed by only manual traction with or without locking stylet were excluded.…”
Section: Lead Extraction In Octogenarian Patients: Effectiveness and ...supporting
confidence: 59%
See 4 more Smart Citations
“…This is in line with the literature, where a comparable success rate was found in patients treated with mechanical dilatation, [17][18][19] with laser extraction and with both techniques, irrespective of older age. [4][5][6][7] Previous studies by Kutarski et al 17 and Jacheć et al 18 with larger study groups compared with our study, demonstrated high effectiveness of TLE using non-powered mechanical tools, suggesting the need of only "simple" mechanical tools in elderly patients, probably due to the absence of significant calcification of connecting tissue scar surrounding leads in octogenarians compared to younger patients. 17,18 However, it should be noted that in our study, the mean implant duration was 112 ± 77 months (range 12-377) and patients with recently implanted leads (implant duration < 12 months) or patients with implant duration > 12 months whose leads had been removed by only manual traction with or without locking stylet were excluded.…”
Section: Lead Extraction In Octogenarian Patients: Effectiveness and ...supporting
confidence: 59%
“…17,18 However, data on lead extraction with a long lead dwell time requiring powered extraction tools are limited in this special patient population. [4][5][6][7] The present multicenter study showed high rates of complete lead extraction and clinically successful lead removal per lead exclusively using the Evolution RL system with ancillary tools as the first-line approach. This is in line with the literature, where a comparable success rate was found in patients treated with mechanical dilatation, [17][18][19] with laser extraction and with both techniques, irrespective of older age.…”
Section: Lead Extraction In Octogenarian Patients: Effectiveness and ...mentioning
confidence: 62%
See 3 more Smart Citations